2007
DOI: 10.1186/1748-717x-2-29
|View full text |Cite
|
Sign up to set email alerts
|

Hypofractionated intensity modulated irradiation for localized prostate cancer, results from a phase I/II feasibility study

Abstract: This hypofractionated IMRT schedule for PC using 25 fractions of 2.64 Gy did not result in severe acute side effects. Until now late urethral, rectal toxicities seemed acceptable as well as failure rates. Detailed analysis of QOL questionnaires resulted in the same conclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 37 publications
3
20
0
1
Order By: Relevance
“…Scores with respect to quality, frequency, and ability to achieve morning erections remained significantly lower at 36 months. The same trend is reflected in data from Namiki et al 27 and Junius et al 25 . Thus, a large number of our patients did not perceive sexual function to be a problem despite significant impairment as discussed by Katz et al 35 .…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Scores with respect to quality, frequency, and ability to achieve morning erections remained significantly lower at 36 months. The same trend is reflected in data from Namiki et al 27 and Junius et al 25 . Thus, a large number of our patients did not perceive sexual function to be a problem despite significant impairment as discussed by Katz et al 35 .…”
Section: Discussionsupporting
confidence: 77%
“…Published comparisons of conventional and hypofractionated radiation schedules for the treatment of prostate cancer indicate that recurrence-free survival is equal or improved with hypofractionation [21][22][23] . Those studies also showed that the qol of prostate cancer patients is either similar or better with the hypofractionated schedules [24][25][26][27][28][29][30] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Grade 2 or greater gu toxicity was found in 32.6% of patients, and grade 2 or greater gi toxicity was seen in 10% of patients. Also, results from a phase i/ii feasibility study of hfrt for localized prostate cancer showed that maximal acute toxicity was reached in weeks 4-5 and resolved within 4 weeks after rt in 82% of the patients 14 . Given that the pattern of toxicity with hfrt appears to peak earlier 14,18,20 , we would recommend a more thorough assessment for signs of acute toxicity during weeks 3-5 of rt.…”
Section: Discussionmentioning
confidence: 99%
“…82-92) and with limited rectal and bladder late complications. [82][83][84][85][86][87][88][89][90][91][92][93][94][95] Reported median follow-up time varied from 19 to 51 months. Publications on prostate cancer patients treated with conventional fractionated EBRT combined with hypofractionated IMRT boosts 96 of 2 fractions of 5-8 Gy (median follow-up of 63 months) or with concomitant boosts 97,98 in 28 fractions of 2.5 Gy and 25 fractions of 2.7 Gy (median follow-up of 46 and 39 months, respectively) concluded that these treatments were feasible and well tolerated.…”
Section: Feasibility Of the Hypofractionation Regimensmentioning
confidence: 99%